Intra-household access to livestock information and financial services in Kenya - Mburu, S.; Njuki, Jemimah; Kariuki, Juliet B. (2012)
Access to timely and reliable information on livestock production and marketing is important in addressing the production and marketing aspects of the sector alongside access to financial services. This study analyzes the intra-household disparities in access to information and financial services among rural households in selected districts in Kenya. Specifically, the study compares women’s access to information on livestock production and financial services with that of men. Results show that informal channels such as farmer to farmer interactions were the key sources of information for livestock production and marketing. More men in male headed households received more training and were exposed to greater and varied topics than women. Men borrowed more from formal credit providers such as banks and co-operatives while women mainly borrowed from their community groups and neighbors. Analysis of determinants of savings by women revealed that women’s age and education positively and significantly increase their probability to save.